Design of FRP reinforced concrete beams for serviceability requirements - Barris, Cristina; Torres, Lluís; Miàs, Cristina; Vilanova, Irene (Journal of Civil Engineering and Management, 2012)
Serviceability Limit States (SLS) may govern the design of concrete elements internally reinforced with Fibre Reinforced Polymer (FRP) bars because of the mechanical properties of FRP materials. This paper investigates the design of Fibre Reinforced Polymer reinforced concrete (FRP RC) beams under the SLS of cracking, stresses in materials, and deflections. A formulation to calculate the bending condition at which crack width and stresses in materials requirements are fulfilled is presented based on principles of equilibrium, strain compatibility and linear elastic behaviour of materials. The slenderness limits to comply with the deflection limitation are redefined and a methodology to calculate the optimal height of an FRP RC beam to satisfy all of these serviceability requirements is proposed. This procedure allows optimising the dimensions of an FRP RC beam taking into account the specific characteristics of the element, such as the mechanical properties of materials and the geometric and loading conditions.